Fatigue with Social Media. Motives for Internet Use and Online and Offline Personality Traits as Moderators (Revista de Psicología, 2024)
Goals: (a) Verify the evidence of construct validity of the Fatigue with Social Media (SMF) Scale, (b) Analyze the relationship between reasons for Internet use (RSU) and FSM and (c) Study the moderation of offline and online personality traits for the relationship between RSU and SMF. The sample was made up of 516 participants residing mostly in the metropolitan area of ​​Buenos Aires and the Buenos Aires suburbs, Argentina (292 men, 224 women); average age: 40.97 years (SD=15.03). Instruments: SMF scale, RSU scale, Big Five Inventory and IACAS Inventory. Results demonstrated that the SMF scale has evidence of construct validity. Additionally, online personality traits such as authenticity, agreeableness/sociability, and cautiousness moderated the relationship between MOTU related to seeking companionship and exhibitionism, and emotional SMF.
Keywords: Internet; Social Media Fatigue; online personality traits; offline personality traits; moderation analysis